Consider a Boolean expression Ex,y,z=(x^-z)v(y^z). Find disjunctive and conjunctive normal form.
Let us find the disjunctive normal form of "E(x,y,z)=(x\\land\\neg z)\\lor(y\\land z)."
"E(x,y,z)=(x\\land\\neg z)\\lor(y\\land z)\n=(x\\land T \\land \\neg z)\\lor(T \\land y\\land z)\n\\\\=(x\\land (y\\lor \\neg y) \\land \\neg z)\\lor((x\\lor\\neg x) \\land y\\land z)\n\\\\=(x\\land y \\land \\neg z)\\lor (x\\land \\neg y\\land \\neg z)\\lor(x \\land y\\land z)\\lor(\\neg x \\land y\\land z)."
It follows that "(x\\land y \\land \\neg z)\\lor (x\\land \\neg y\\land \\neg z)\\lor(x \\land y\\land z)\\lor(\\neg x \\land y\\land z)" is a disjunctive normal form of "E(x,y,z)."
Let us find the conjunctive normal form of "E(x,y,z)=(x\\land\\neg z)\\lor(y\\land z)."
"E(x,y,z)=(x\\land\\neg z)\\lor(y\\land z)\n=(x\\lor y)\\land(x\\lor z)\\land (\\neg z\\lor y)\\land (\\neg z\\lor z)\n\\\\=(x\\lor y\\lor F)\\land(x\\lor F\\lor z)\\land ( F\\lor y\\lor \\neg z)\\land T\n\\\\=(x\\lor y\\lor (\\neg z\\land z))\\land(x\\lor (\\neg y\\land y)\\lor z)\\land ( (\\neg x\\land x)\\lor y\\lor \\neg z)\n\\\\=(x\\lor y\\lor \\neg z)\\land(x\\lor y\\lor z)\\land(x\\lor \\neg y\\lor z)\\land(x\\lor y\\lor z)\\land ( \\neg x\\lor y\\lor \\neg z)\\land ( x\\lor y\\lor \\neg z)\n\\\\=(x\\lor y\\lor \\neg z)\\land(x\\lor y\\lor z)\\land(x\\lor \\neg y\\lor z)\\land ( \\neg x\\lor y\\lor \\neg z)."
It follows that "(x\\lor y\\lor \\neg z)\\land(x\\lor y\\lor z)\\land(x\\lor \\neg y\\lor z)\\land ( \\neg x\\lor y\\lor \\neg z)" is a conjunctive normal form of "E(x,y,z)."
Comments
Leave a comment